The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1111/j.1540-8159.1995.tb02505.x
|View full text |Cite
|
Sign up to set email alerts
|

Large Capacitor Defibrillation Waveform Reduces Peak Voltages Without Increasing Energies

Abstract: The 500 microF, long duration waveform reduced peak voltage 41% (374 +/- 18 V [STD] vs 219 +/- 14 V [LD], P < 0.001) and reduced peak current 38% (11.0 +/- 1.1 A [STD] vs 6.8 +/- 0.6 A [LD], P < 0.001) but did not significantly change the delivered energy (12.4 +/- 1.3 J [STD] vs 13.4 +/- 1.0 J [LD]). Durations increased from 10.0 +/- 0.2 to 17.6 +/- 0.5 msec (P < 0.001).(ABSTRACT TRUNCATED AT 250 WORDS)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2001
2001

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…We chose the 300-F capacitor because it has been shown that large-capacitor waveforms reduce DFT peak voltage without increasing DFT energy. 29,30 Reducing peak voltage may decrease detrimental shock effects and may allow lower voltage ratings of the electronic components in the defibrillator, which would allow the size of the components to be reduced.…”
Section: Study Limitationsmentioning
confidence: 99%
“…We chose the 300-F capacitor because it has been shown that large-capacitor waveforms reduce DFT peak voltage without increasing DFT energy. 29,30 Reducing peak voltage may decrease detrimental shock effects and may allow lower voltage ratings of the electronic components in the defibrillator, which would allow the size of the components to be reduced.…”
Section: Study Limitationsmentioning
confidence: 99%